Figurative Language in Bullet For My Valentine Album “Scream Aim Fire” - Astini, Ni Luh Cintya Sandi; Dewi, A. A. Sg. Shanti Sari; Sukarini, Ni Wayan (Humanis; Vol 23 No 4 (2019)DO - 10.24843/JH.2019.v23.i04.p02, 2019)
The study entitled “Figurative Language in Bullet For My Valentine’s Album Scream Aim Fire” is aimed at finding out and identifying the types of figurative language, especially personification and hyperbole, in Bullet For My Valentine’s Album, Scream Aim Fire, and analyzing the meaning. The documentation method was used to collect the data, and to analyze the data, the qualitative method was applied. This research applied the theory of Types of Figurative Language proposed by Knickerbocker and Renninger (1963) to find and identify personification and hyperbolic expressions from the album, and Types of Meaning according to Leech (1974) to classify and analyze the meaning of personification and hyperbolic expressions. The study indeed focuses on personification and hyperbole only because both are the most common expressions/figurative languages used by the songwriters to personate particular objects or stress and exaggerate their words on the song they write to make it more beautiful, dramatic, and meaningful. 14 out of 15 songs of the Scream Aim Fire album used both personification and hyperbole in their lyrics. 12 of them used both personification and hyperbole, one of them used only personification, one of them used only hyperbole, and the last one used neither of them. As for the types of meaning, there were connotative meaning, affective meaning, thematic meaning, and reflective meaning.